International organizations as orchestrators - Abbott, Kenneth W. (Cambridge : Cambridge University Press, 2015)
International Organizations as Orchestrators reveals how IOs leverage their limited authority and resources to increase their effectiveness, power, and autonomy from states. By'orchestrating' intermediaries - including NGOs - IOs can shape and steer global governance without engaging in hard, direct regulation. This volume is organized around a theoretical model that emphasizes voluntary collaboration and support. An outstanding group of scholars investigate the significance of orchestration across key issue areas, including trade, finance, environment and labor, and in leading organizations, including the GEF, G20, WTO, EU, Kimberley Process, UNEP and ILO. The empirical studies find that orchestration is pervasive. They broadly confirm the theoretical hypotheses while providing important new insights, especially that states often welcome IO orchestration as achieving governance without creating strong institutions. This volume changes our understanding of the relationships among IOs, nonstate actors and states in global governance, using a theoretical framework applicable to domestic governance.
Machine generated contents note: Part I. Introduction: 1. Orchestration: global governance through intermediaries Kenneth W. Abbott, Philipp Genschel, Duncan Snidal and Bernhard Zangl; Part II. Managing States: 2. Orchestrating policy implementation: EU governance through regulatory networks Michael Blauberger and Berthold Rittberger; 3. Orchestration on a tight leash: state oversight of the WTO Manfred Elsig; 4. Orchestration by design: the G20 in international financial regulation Lora Anne Viola; 5. Efficient orchestration? The global environment facility in the governance of climate adaptation Erin Graham and Alexander Thompson; 6. Orchestrating monitoring: the optimal adaptation of international organizations Xinyuan Dai; 7. Orchestrating enforcement: international organizations mobilizing compliance constituencies Jonas Tallberg; Part III. Bypassing States: 8. WHO orchestrates? Coping with competitors in global health Tine Hanrieder; 9. Orchestrating peace? Civil war, conflict minerals, and the United Nations Security Council Virginia Haufler; 10. Governing where focality is low: UNEP and the principles for responsible investment Cornis van der Lugt and Klaus Dingwerth; 11. Orchestration for the'social partners' only: internal constraints on the ILO Lucio Baccaro; 12. Orchestrating the fight against anonymous incorporation: a field experiment Michael Findley, Daniel Nielson and J. C. Sharman; Part IV. Implications: 13. Orchestration along the pareto frontier: winners and losers Walter Mattli and Jack Seddon; 14. Orchestrating global governance: from empirical results to theoretical implications Kenneth W. Abbott, Philipp Genschel, Duncan Snidal and Bernhard Zangl.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: International agencies -- Decision making; International organization -- Decision making; International cooperation